bZIP transcription factor zip-2 mediates an early response to Pseudomonas aeruginosa infection in Caenorhabditis elegans - Estes, Kathleen A. (National Academy of Sciences, 2010)

(untitled)
Very little is known about how animals discriminate pathogens from innocuous microbes. To address this question, we examined infection-response gene induction in the nematode Caenorhabditis elegans. We focused on genes that are induced in C. elegans by infection with the bacterial pathogen Pseudomonas aeruginosa, but are not induced by an isogenic attenuated gacA mutant. Most of these genes are induced independently of known immunity pathways. We generated a GFP reporter for one of these genes, infection response gene 1 (irg-1), which is induced strongly by wild-type P. aeruginosa strain PA14, but not by other C. elegans pathogens or by other wild-type P. aeruginosa strains that are weakly pathogenic to C. elegans. To identify components of the pathway that induces irg-1 in response to infection, we performed an RNA interference screen of C. elegans transcription factors. This screen identified zip-2, a bZIP transcription factor that is required for inducing irg-1, as well as several other genes, and is important for defense against infection by P. aeruginosa. These data indicate that zip-2 is part of a specialized pathogen response pathway that is induced by virulent strains of P. aeruginosa and provides defense against this pathogen.